Cytogenetic characterization of Sambalpuri and Manda buffaloes of Odisha - KUMAR, LAVA; SINGH, RAVINDER; NIRANJAN, S K; KUMAR, PREM; VOHRA, V; DASH, S K; KATARIA, R S (The Indian Journal of Animal Sciences, 2019)
Cytogenetics analysis even though mostlyused for the evaluation of chromosomal abnormality by arresting the cell division at metaphase stage, but is also helpful to ascertain the riverine/swamp status of buffaloes. The study was conducted to characterize two buffalo populations, viz. Sambalpuri and Manda of Odisha cytogenetically, to establish their riverine or swamp status. Metaphase chromosome spreads ofboth, Sambalpuri and Manda buffaloes showed a chromosome number of 2n=50.There were fivepairs of metacentric or sub-metacentric and 19 pairs acrocentric along with a pair of sex chromosomesin both the populations, typical of riverine buffalo. Nomorphological or chromosomal abnormality observed in any of the populations. This study thus confirms the riverine status of both the Odisha buffalo populations.